Impact of China’s rise on the Mekong region - Yos Santasombat (2018)
© Yos Santasombat, 2015. This volume presents a contemporary analysis of the impact of China's rise on the Mekong Region at a critical point in Southeast Asian history. As the most populated country and the second largest economy in the world, China has become an increasingly influential player in global and regional affairs in recent decades. Economic ties between China and her southern neighbors are particularly strong. Yet relations between China and the Mekong region are embedded in complex socio-cultural and political issues. China's accelerated growth, increasing economic footprint, rapid military modernization, and global search for energy, natural resources, and food security have created a wide range of new challenges for smaller countries in Southeast Asia. These new challenges both encourage and limit cooperation between China and the emerging ASEAN Economic Community (AEC). The authors pay close attention to these challenges with particular focus on the impact of Chinese investment, trade, foreign aid, and migration.